A Systematic Review of Delirium Biomarkers and Their Alignment with the NIA‐AA Research Framework. Issue 1 (25th September 2020) - Wang, Sophia; Lindroth, Heidi; Chan, Carol; Greene, Ryan; Serrano‐Andrews, Patricia; Khan, Sikandar; Rios, Gabriel; Jabbari, Shiva; Lim, Joanna; Saykin, Andrew J.; Khan, Babar
Abstract : OBJECTIVES: To identify whether delirium biomarkers aligned with the National Institute on Aging–Alzheimerʼs Association (NIA‐AA) research framework, a conceptual model that describes the use of diagnostic biomarkers for Alzheimerʼs disease and other related dementias (ADRD). DESIGN: Systematic review following Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. SETTING: Acute care and outpatient settings. PARTICIPANTS: Adults diagnosed with delirium. METHODS AND MEASUREMENTS: MEDLINE, PsycInfo, Embase, and the Cochrane Library were searched for English‐language studies published from January 2010 to February 2020. Studies included adults older than 18 years, identified delirium with a standardized assessment tool, and measured an ADRD biomarker. Independent reviewers determined whether an association between delirium and ADRD biomarker was found, the quality of biomarker data based on the REMARK (REporting recommendations for tumor MARKer prognostic studies) checklist, and the study bias based on the Newcastle‐Ottawa Scale. RESULTS: A total of 61, 256 citations were identified; 113 studies were included. Most studies did not examine amyloid, tau, or neurodegeneration biomarkers. Delirium may be associated with neurodegeneration biomarkers, but few to no studies found an association with amyloid and tau biomarkers. Delirium was not consistently associated with inflammatory biomarkers. The quality of biomarker data was moderate, and the risk of bias was moderate to high. Studies often did not collect prehospital and posthospital cognitive data. CONCLUSION: Most delirium diagnostic biomarker studies did not measure amyloid, tau, and/or neurodegenerative biomarkers, making characterization of the relationship between delirium and ADRD difficult. Future delirium biomarker diagnostic studies could improve the understanding of pathophysiologic links between delirium with other conditions affecting cognition.